Quarternary Lateritizations stages in Viet Nam - Hiển, Đậu; Tự, Đỗ Văn; Hà, Vũ Văn (Vietnam Journal of Earth Sciences, 2018)
The products of lateritization in Viet Nam are mainly formed in 3 stages....